2017
DOI: 10.1021/acs.jpcb.7b07386
|View full text |Cite
|
Sign up to set email alerts
|

Low-Temperature Dynamics of Chain-Labeled Lipids in Ester- and Ether-Linked Phosphatidylcholine Membranes

Abstract: Continuous wave electron paramagnetic resonance spectroscopy and two-pulse echo detected spectra of chain-labeled lipids are used to study the dynamics of frozen lipid membranes over the temperature range 77-260 K. Bilayers of ester-linked dihexadecanoylphosphatidylcholine (DPPC) with noninterdigitated chains and ether-linked dihexadecyl phosphatidylcholine (DHPC) with interdigitated chains are considered. Rapid stochastic librations of small angular amplitude are found in both lipid matrices. In noninterdigit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
8
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 48 publications
1
8
0
Order By: Relevance
“…Regarding the CW EPR data, for the spin-labeled DPPC bilayer the value was found to start to increase above 200 K [ 19 ], which is also in agreement with data in Figure 4 for lysozyme. For spin-labeled DOPC bilayer, when the spin label is located near the bilayer surface, the value starts to increase at 240 K [ 28 ].…”
Section: Discussionsupporting
confidence: 82%
See 3 more Smart Citations
“…Regarding the CW EPR data, for the spin-labeled DPPC bilayer the value was found to start to increase above 200 K [ 19 ], which is also in agreement with data in Figure 4 for lysozyme. For spin-labeled DOPC bilayer, when the spin label is located near the bilayer surface, the value starts to increase at 240 K [ 28 ].…”
Section: Discussionsupporting
confidence: 82%
“…To further support the suggested explanation of the kink for the Δ W temperature dependence for casein near 120 K as evidence for the disorder–order transition, we turn to comparison with the analogous ESE studies of stochastic molecular librations in spin-labeled gel-phase phospholipid bilayers composed either of conformationally ordered or conformationally disordered lipids. These studies were performed for the bilayers composed of saturated 1,2-dipalmitoyl- sn -glycero-3-phosphocholine (DPPC) lipids [ 16 , 19 , 28 ], mono-unsaturated 1-palmitoyl-2-oleoyl- sn -glycero-3-phosphocholine (POPC) lipids [ 16 , 28 ] doubly-unsaturated 1,2-dioleoyl- sn -glycero-3-phosphocholine (DOPC) lipids [ 17 , 28 ]. In these systems, DPPC presents an example of conformationally ordered molecule while POPC and DOPC are conformationally disordered.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…34,35 It was shown that these motions participate in the collective motion of the surroundings 35 and are determined by the nearest nanoscale surrounding of the spin-labeled molecule. 37–39 On these grounds, these motions may deliver unique information on the rigidity of nanoscale molecular packing in the molecular systems under study. Except for the mentioned above ILs, nanoscale molecular packing was studied with pulsed EPR for model biological membranes (lipid bilayers) 37–42 and for proteins.…”
Section: Introductionmentioning
confidence: 99%